Working-Class Mobility and Streetcar Politics in Reconstruction-Era St. Louis. Issue 1 (2nd January 2022) - Belanger, Elizabeth
Abstract : This article explores seven segregation cases involving African-American women and public transportation that played out in the city courts of St. Louis between 1865 and 1871. Situating the cases within a theoretical framework of mobility, the article explores the spatial characteristics of African-American working-class women's lives and the extent to which streetcars became staging grounds for larger civil rights battles. While previous accounts of streetcar activism have often positioned cases as isolated incidents undertaken by elite African-American women, the cases in St. Louis attest to the rise of civil rights activism among working-class African-American women. The discussion further shows how they contributed to the nature and form of oppositional politics in St. Louis.